Comportamento do sorgo granífero em função do manejo de nitrogênio - Silva, Pedro Celso Soares da (2004)
The objective of this study was to define the adequate management of the nitrogen fertilization in the culture of grain sorghum, using as source the urea in soil of average texture. In the experiment conducted in 2001/02, was used a population density of 171,000 plants/ha-1, in direct plantation and was characterized by little precipitation. The assay realized in the agricultural year of 2002/03, was characterized by raised precipitation and was used 214,000 plants/ha-1, in conventional plantation. The experimental design was a randomized block with three repetitions and had been constituted by 21 treatments with nitrogen: 200 kg N/ha-1 in the base; 150 kg N/ha-1 in the base more 50 kg N/ha-1 on top on the 20, 44, 55, 66 and 74 days after the emergency of the plants; 100 kg N/ha-1 in the base more 100 kg N/ha-1 on top on the 20, 44, 55, 66 and 74 days after the emergency of the plants; 50 kg N/ha-1 in the base more 150 kg N/ha with on top on the 20, 44, 55, 66 and 74 days after the emergency of the plants; 200 kg N/ha-1 on top on the 20, 44, 55, 66 and 74 days after the emergency of the plants. In relation to the management with nitrogen fertilization in the of grain sorghum arrived the following: the treatments with 50 kg N/ha-1 in the base more 150 kg/ha-1 on top on the 66 and 74 days and 200 kg N/ha-1 on top on the 66 and 74 days in the low precipitation conditions of the agricultural year of 2001/02, had presented the lowest values of index of foliar area, biological productivity and grain yield; the nitrogen fertilization in the high precipitation conditions, registered in the agricultural year of 2002/03, provided to high index of foliar area and grain yield in hall the applied treatments; in experiment 2001/02, o the number of grains for panicle was the variable that more influenced in the grain yield and in 2002/03 it was the harvest index; by that is was observed in terms of grain yield, it could be said that good distribution of rain, the manegement with 200 kg N/ha-1 could be made until the 74 days the emergency, that would not reduce the productivity of grains